Contribution of five major apple polyphenols in reducing peanut protein sensitization and alleviating allergencitiy of peanut by changing allergen structure. (February 2023) - Sun, Shanfeng; Jiang, Tianyi; Gu, Yanjun; Yao, Lu; Du, Hang; Luo, Jiangzuo; Che, Huilian
Graphical abstract: Highlights: All five major apple polyphenols (epicatechin, phlorizin, rutin, chlorogenic acid, and catechin) could reduce the sensitization of peanut protein. Epicatechin had the strongest inhibitory effect among the five major apple polyphenols. Polyphenol binding could alleviate allergencitiy of peanut and regulate MAPK related signaling pathway. The combination of epicatechin with constitutive epitopes arginine led to spatial structure changes of Ara h 1. The reduction of peanut protein sensitization might due to the effective linear epitope reduction caused by structure change of peanut allergen. Abstract: Peanuts are prone to trigger allergic reactions with high mortality rate. There is currently no effective way to prevent peanut allergy. In order to reduce the allergy risk of peanuts, it's significant to reduce sensitization of peanut prior to ingestion. In this study, the effects of five major apple polyphenols (epicatechin, phlorizin, rutin, chlorogenic acid, and catechin) -peanut protein on the sensitization of peanut allergens were studied by BALB/c peanut allergy model to access the contribution of each polyphenol in apple to peanut allergen sensitization reduction. Then, the mechanism was explored in terms of the effect of polyphenols on the simulated gastric digestion of peanut protein and the changes in structure of Ara h 1. The results showed that polyphenol binding could alleviate allergencitiy of peanut and regulate MAPK related signaling pathway. Among the five major apple polyphenols, epicatechin had the strongest inhibitory effect. The binding of epicatechin to the constitutive epitopes arginine led to changes in the spatial structure of Ara h 1, which resulted in the effective linear epitopes reduction. Modification of peanut allergens with polyphenols could effectively reduce the sensitization of peanut protein.